Feasibility Analysis of Seaweed (Eucheuma cottoni) Farming in Takatidung Village, Polewali Subdistrict, Polewali Mandar Regency - Irma Yulia Madjid; Turjaun Turjaun; Chairul Rusyd Mahfud (Jurnal Perikanan Terpadu, 2025)
The cultivation of Eucheuma cottonii seaweed has experienced significant growth and has played an important role in driving the coastal community’s economy, particularly among small-scale farming groups. However, due to the limited number of feasibility studies, farmers often rely on trial-and-error methods without proper economic planning. This can lead to financial risks, especially when market prices drop or production is disrupted. This study aims to determine the feasibility of seaweed farming in Takatidung Village, Polewali Subdistrict, Polewali Mandar Regency, using interview methods. The population in this study consists of coastal communities who are permanent residents working as seaweed farmers. A purposive sampling method was used by taking a sample of 10% from a total of 50 seaweed farming groups. Therefore, 5 farmer groups were selected as respondents in this study. The business analysis methods used include Income Analysis, Return Cost Ratio (R/C) Analysis, Benefit Cost Ratio (B/C) Analysis, and Break-Even Point (BEP) Analysis. The total income of the selected groups was as follows: Harapan Baru Group IDR 8,544,000, Mawar Melati Group IDR 6,344,000, Marannu Group IDR 8,531,000, Tanjung Biru Group IDR 8,514,000, and Semua Jaya Group IDR 8,531,000. The average Return Cost Ratio (R/C) value was greater than 1, at 2.32, indicating that for every IDR 1 spent, a return of 2.32 times the cost was obtained. This means the business is profitable and feasible for further development. The average Benefit Cost Ratio (B/C) value was also greater than 1, at 1.32, meaning that for every IDR 1 spent, a net benefit of IDR 1.32 was obtained, indicating that the business is feasible and provides benefits. The Break-Even Point (BEP) analysis in terms of revenue, production, and price showed values at the break-even point. The overall results of this study indicate that seaweed farming in Takatidung Village, Polewali Subdistrict, Polewali Mandar Regency, is profitable and feasible to continue as a business venture